Perancangan Sistem Informasi Berbasis Web untuk Pengelolaan Pemesanan dan Produksi pada UMKM Konveksi CV. Florence Collection - Surbakti, Feliks Prasepta Sejahtera; Billie Tiandri, Bernardus; B.Wahju, Marsellinus (Metris: Jurnal Sains dan Teknologi, 2025)
The development of information technology has impacted current business behavior, affecting both users (customers) and business owners. Everyone is competing to maximize the use of information technology, whether to facilitate transactions or to improve business management efficiency. This situation is also experienced by CV. Florence Collection, a micro, small, and medium enterprise (MSME) operating in the garment industry, which faces several challenges in managing its business using a manual system. For instance, customer and transaction records are managed using Microsoft Excel, resulting in manually generated reports that are prone to recording errors. Additionally, customers have limited access to information during the ordering process, and payment verification by the business owner is not efficient. Based on these challenges, this study proposes the design of a web-based system for managing the operations of CV. Florence Collection. The system design follows the System Development Life Cycle (SDLC) method, consisting of four stages: planning, analysis, design, and implementation, using PHP as the programming language and MySQL as the database. The proposed system is tested using the blackbox testing method. The designed information system can be implemented by incurring implementation costs, such as hosting, domain, maintenance, and development expenses.